Híbrido de milho de maior aceitabilidade no sul de Minas Gerais - Coelho, Ricardo Flabes de Castro (2010)
The new technologies tend to affect in different ways the agricultural explorations, the farmers and the areas where those activities grow. In this context, the objective of this research was to describe and to identify the profile of the hybrid of larger acceptability developed by the companies sowings that act at the market of the south of Minas Gerais. To present research it was based in the analysis of the primary data collected the companies sowings that act cooperatives close to close to, companies correlate and producing of corn of the area of the south of Minas Gerais. These companies were: Dekalb (São Paulo); Agromen Sementes (São Paulo); Syngenta Seeds (São Paulo); Seeds Dow Agro Sciences Ltda (São Paulo); Pioneer (Rio Grande do Sul); Biomatrix (Minas Gerais); Agroceres (São Paulo); Agroeste (São Paulo); Saint Helena Sementes S.A. (Minas Gerais). Para the accomplishment of the referred research, they were used bibliographical research, researches in specialized sites, random sample, rising of data, questionnaire and field research with the qualitative method. It was ended that the profile of the hybrid more I accept, developed by the companies sowings would be: the precocious double hybrid with couple aptitude, grains semi hard of color it yellows, with plant of medium load tends high resistance to the lodging, preferably positioned in normal time and with possibility to answer satisfactorily to a high investment in the culture.